Consortium-Based Science: The NIEHS's Multipronged, Collaborative Approach to Assessing the Health Effects of Bisphenol A. - Birnbaum, Linda S.; Bucher, John R.; Collman, Gwen W.; Zeldin, Darryl C.; Johnson, Anne F.; Schug, Thaddeus T.; Heinde, Jerrold J. (Environmental Health Perspectives, 2012)
BACKGROUND: Bisphenol A (BPA) is a high production volume chemical used to make polycarbonate plastic and is found in many consumer products. Some studies using animal models have suggested that BPA exposures may have adverse health effects. However, research gaps have precluded a full understanding of the effects of BPA in humans and engendered controversies surrounding the chemical's potential toxicity. OBJECTIVES: The National Institute of Environmental Health Sciences (NIEHS) and National Toxicology Program (NTP) have developed an integrated, multipronged, consortium-based approach to optimize BPA-focused research investments to more effectively address data gaps and inform decision making. DISCUSSION: NIEHS/NTP BPA research investments made over the past 4 years include extramural research grants, establishment of a BPA Grantee Consortium, intramural research activities on BPA's mechanisms of action, the launch of two clinical studies and an occupational study, development of a round-robin experiment to validate BPA measurements in human serum, and, in collaboration with the Food and Drug Administration (FDA), formation of a consortium to design and execute a chronic toxicity study of BPA in rats. The NIEHS's new consortium-based approach has led to more integrated, collaborative efforts and should improve our ability to resolve controversies over the potential human health effects of exposures to low levels of endocrine-active agents.